PENGEMBANGAN ARBORETUM TANAMAN TARUPREMANA UNTUK MENINGKATKAN DAYA TARIK WISATA DI DESA TARO KECAMATAN TEGALLALANG KABUPATEN GIANYAR - I.D.P. Singarsa; I.K. Sardiana; W.P. Windia; K.K. Dinata (Buletin Udayana Mengabdi, 2018)
The Community service activities aimed is to develop arboretum of taru Premana plant to increase theattractiveness of tourist village of Taro, District Tegallalang, Gianyar. The method applied in this communityempowerment, among others: (1) Coordination and participatory communication with village leaders andvillagers taro to formulate a program from the planning, operational and evaluation; (2) Counseling on theimportance of the development of the arboretum taru premana and travel awareness groups to manage thetourism potential of the village; (3) planting taru premana accordance trihita karana philosophy; (4)Assistance is meeting regularly and sustainably among companion with target communities. The resultsshowed that the arboretum “taru premana” plant development activities have been going well. The numberof plants taru Premana that can be planted as many as 1,000 trees, consists of nine types, ie 400 trees ofcoconut daksina and 600 trees of the wood are sandalwood, nagasari, nutmeg, cempaka, mundeh, kwanitan,Rijasa, and majegau. People respond positively to community service activities are carried out as inaccordance with the potential and needs of the community.